Heath risk behaviours among adolescents in central of Vietnam: a cross sectional study - Ton, Nu Minh Duc; Tran, Thi Hang; Ha, Van Anh Bao; Ho, Thi Thuy Trang; Mai, Ba Hai; Tran, Thi Nguyet; Vo, Thi Diem Binh; Hoang, Thi Viet Ha; Nguyen, Vu Quoc Huy; Nguyen, Thi Anh Phuong (Tạp chí Y Dược Huế, 2022)
Background: Adolescence is vulnerable subjects and faces many risks that greatly impact their health and development in the future, but adolescents are not really getting the proper care from the health care system. This study aimed to examine the prevalence of health risk behaviours among adolescents in Thua Thien Hue Province, Vietnam, and to determine related factors to adolescents’ health risk behaviours. Materials and Methods: A descriptive cross-sectional study was conducted on 934 adolescents in Thua Thien Hue province, with a multi-stage sampling method. The Youth Risk Behaviour Survey of the Center for Disease Control and Prevention was used for data collection in this study. The SPSS 20.0 software was used to analyse data. Results: The proportion of overweight-obesity adolescents accounted for 14.6%. The prevalence of adolescent bullying was 14.0%, the higher the adolescent high, the lower the risk of bullying (OR=0.981, p=0.03). The proportion of smoking was low (2.8%), while the alcohol use rate accounted for 10.0%. Adolescents in high school have a higher risk of smoking and alcohol use than those in secondary school. The proportion of adolescents who attempted suicide was slightly high (16.0%). Adolescents who felt lonely, whose parents did not know what the adolescent did in their free time, and does not respect them were several factors that increase suicide intention. Conclusions: School adolescent violence, overweight- obese status, alcohol use, smoking, and suicide intention are health problems occurring among adolescents in Thua Thien Hue. Besides, the feeling of loneliness increases the risk of suicide intention. Adolescents need to receive proper attention from their parents, as well as the healthcare system.